Physiological Network Is Disrupted in Severe COVID-19 - Barajas-Martínez, Antonio; Mehta, Roopa; Ibarra-Coronado, Elizabeth; Fossion, Ruben; Martínez Garcés, Vania J.; Arellano, Monserrat Ramírez; González Alvarez, Ibar A.; Bautista, Yamilet Viana Moncada; Bello-Chavolla, Omar Y.; Pedraza, Natalia Ramírez; Encinas, Bethsabel Rodríguez; Carrión, Carolina Isabel Pérez; et al. (Frontiers in Physiology, 2022)
The human body is a complex system maintained in homeostasis thanks to the interactions between multiple physiological regulation systems. When faced with physical or biological perturbations, this system must react by keeping a balance between adaptability and robustness. The SARS-COV-2 virus infection poses an immune system challenge that tests the organism's homeostatic response. Notably, the elderly and men are particularly vulnerable to severe disease, poor outcomes, and death. Mexico seems to have more infected young men than anywhere else. The goal of this study is to determine the differences in the relationships that link physiological variables that characterize the elderly and men, and those that characterize fatal outcomes in young men. To accomplish this, we examined a database of patients with moderate to severe COVID-19 (471 men and 277 women) registered at the “Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán” in March 2020. The sample was stratified by outcome, age, and sex. Physiological networks were built using 67 physiological variables (vital signs, anthropometric, hematic, biochemical, and tomographic variables) recorded upon hospital admission. Individual variables and system behavior were examined by descriptive statistics, differences between groups, principal component analysis, and network analysis. We show how topological network properties, particularly clustering coefficient, become disrupted in disease. Finally, anthropometric, metabolic, inflammatory, and pulmonary cluster interaction characterize the deceased young male group.